Moral values in small organizations - Lennick, Doug; Kiel, Fred; Kiel, Fred; Lennick, Doug (Upper Saddle River, N.J. FTPress Delivers, 2011)
"This Element is an excerpt from Moral Intelligence: Enhancing Business Performance and Leadership Success (ISBN: 9780132349864) by Doug Lennick and Fred Kiel. The unique challenges of morality in small business: building the small company that lives by the principles of integrity, responsibility, compassion, and forgiveness"--Resource description page
Includes bibliographical references
Keywords: Leadership / Aspect moral; Leadership / Moral and ethical aspects / fast / (OCoLC)fst00994713; Morale des affaires; Business ethics / blmlsh; Success in business / Moral and ethical aspects / blmlsh; BUSINESS & ECONOMICS / Business Ethics / bisacsh; Success in business / Moral and ethical aspects; Succès dans les affaires / Aspect moral; Small business / Management / fast / (OCoLC)fst01121306; Business ethics / http://id.loc.gov/authorities/subjects/sh85018297; Small business / Management / http://id.loc.gov/authorities/subjects/sh85123576; Leadership / Moral and ethical aspects; Business ethics / fast / (OCoLC)fst00842675; Petites et moyennes entreprises / Gestion; Small business / Management / blmlsh; Leadership / Moral and ethical aspects / blmlsh